Classifying Adjoint Pairs and Adjoint Triples in an Atanassov L-Fuzzy Framework. - Krídlo, Ondrej; Ojeda-Aciego, Manuel (IEEE, 2022)
We study and classify a family of adjoint pairs and adjoint triples for Atanassov L-fuzzy framework based on a complete residuated lattice satisfying the double negation law.
https://openpolicyfinder.jisc.ac.uk/id/publication/3451
Keywords: Conjuntos difusos; Monoides; Algebra abstracta; Adjoint pair; Adjoint triple; Atanassov L-fuzzy sets; Girard monoid